Redox-active benzoquinone-intercalated layered vanadate for high performance zinc-ion battery: Phenol-keto conversion and the anchoring effect of V-O-V host framework. (20th December 2022) - Liu, Chang Lin; Cao, Tong; Wang, Zhao Peng; Li, Kai; Gong, Yun; Zhang, Da Liang
Highlights: ( o -BQ)0.25 V2 O5 ·0·5H2 O and ( p -BQ)0.25 V2 O5 ·0·5H2 O (BQ = benzoquinone) were synthesized. Rietveld refinements and HAADF-STEM reveal the successful intercalation of BQ into V2 O5 . ( p -BQ)0.25 V2 O5 ·0·5H2 O shows an excellent rate performance and an ultralong cycle life. The sandwiched BQ in layered V2 O5 can be prevented from leaching into the electrolyte. DFT calculations disclose a small Zn 2+ -migration barrier in ( p -BQ)0.25 V2 O5 · x H2 O. Abstracts: Utilizing a facile one-step hydrothermal technique, oxygen-deficient ( o -BQ)-VO and ( p -BQ)-VO nanosheets were synthesized, which were formulated as ( o -BQ)0.25 V2 O5 ·0·5H2 O and ( p -BQ)0.25 V2 O5 ·0·5H2 O (BQ = benzoquinone), respectively. Rietveld refinements and high-angle annular dark-field (HAADF)-scanning transmission election microscope (STEM) reveal the successful intercalation of o -BQ or p -BQ into the layered V2 O5 with large interlayer spacings of ∼ 13.7 Å, in which all the V centers are coordinatively unsaturated due to the elongation of V-O bonds. ( p -BQ)-VO shows an excellent rate performance of 487/446/405/371/333/280 mAh g −1 at 0.1 ∼ 5 A g −1 and an ultralong cycle life with a capacity retention of 96.0% after 4000 discharge/charge cycles at 5 A g −1, which is due to the dual redox-activity from BQ and vanadium oxide. The phenol-keto conversion of BQ can provide extra capacity. Furthermore, the sandwiched BQ in layered V2 O5 can be prevented from leaching into the electrolyte. On the other hand, ( p -BQ)-VO shows better electrochemical performance than ( o -BQ)-VO, indicating that the redox property of quinone is associated with the para - or ortho -position of keto-group and their possible coordination modes with Zn 2+ . Density functional theory (DFT) calculations disclose that the deep intercalation of Zn 2+ on certain site in ( p -BQ)-VO can improve electron conductivity, giving rise to enhanced electrochemical behavior. And the Zn 2+ -migration along b axis of the ( p -BQ)-VO cell shows a small energy barrier of 0.80 eV, thus leading to the outstanding rate and cycling performances. Graphical abstract: Redox-active benzoquinone (BQ)-intercalated layered vanadate ( p -BQ)0.25 V2 O5 ·0·5H2 O exhibits excellent rate performance and ultralong cycle life in zinc-ion battery, which is due to the dual redox-activity from BQ and vanadium oxide. Furthermore, the sandwiched BQ in layered V2 O5 can be prevented from leaching into the electrolyte. DFT calculations disclose a small Zn 2+ -migration barrier of 0.80 eV. Image, graphical abstract